Case report: Acute severe hyponatremia-induced seizures in a newborn: a community-acquired case and literature review - Li, Haiting; Chen, Xiyang; Chen, Linlin; Li, Jie; Liu, Xixi; Chen, Caie; Xie, Dengpan; Yuan, Junhui; Tao, Enfu (Frontiers in Pharmacology, 2024)
Severe neonatal hyponatremia represents a critical electrolyte imbalance with potentially severe neurological outcomes, a condition rarely documented in community-acquired, full-term newborns. This report underscores a unique case of a 23-day-old, previously healthy, full-term male neonate experiencing severe hyponatremia that precipitated seizures, underscoring the urgency of prompt recognition and intervention. The neonate presented with symptoms including vomiting, groaning, chills, fixed staring, and limb tremors. Critical findings upon admission encompassed hypothermia, hypotension, tachycardia, and tachypnea accompanied by significant weight loss. The clinical presentation was marked by dehydration, lethargy, weak crying, a fixed gaze, irregular breathing, and coarse lung sounds, yet a distended abdomen, hypertonic limb movements, and recurrent seizures were observed. Immediate interventions included establishing IV access, rewarming, mechanical ventilation, seizure management, volume expansion, dopamine for circulatory support, and initiation of empirical antibiotics. Diagnostic evaluations revealed a sodium ion concentration of 105.9mmol/L, while amplitude-integrated electroencephalography (aEEG) detected pronounced seizure activity characterized by a lack of sleep-wake rhythmicity, noticeable elevation in both the lower and upper amplitude margins, and a sustained decrease in the lower margin voltage dropping below 5 μV, presenting as sharp or serrated waveforms. The management strategy entailed rapid electrolyte normalization using hypertonic saline and sodium bicarbonate, anticonvulsant therapy, and comprehensive supportive care, with continuous aEEG monitoring until the cessation of seizures. Remarkably, by the third day, the neonate's condition had stabilized, allowing for discharge in good health ten days post-admission. At a 16month follow-up, the child exhibited no adverse neurological outcomes and demonstrated favorable growth and development. Our extensive review on the etiology, clinical manifestations, aEEG monitoring, characteristics of seizures induced by severe neonatal hyponatremia, treatment approaches, and the prognosis for seizures triggered by severe hyponatremia aims to deepen the understanding and enhance clinical management of this complex condition. It stresses the importance of early detection, accurate diagnosis, and customized treatment protocols to improve outcomes for affected neonates. Additionally, this review accentuates the indispensable role of aEEG monitoring in managing neonates at elevated risk for seizures. Yet, the safety and efficacy of swiftly administering hypertonic saline for correcting severe hyponatremiainduced seizures necessitate further investigation through medical research.